Distribution of Word Classes in Old English and Old High German: a Preliminary Contrastive Study Based on „The Battle of Maldon”, „Hildebrandslied” and „Ludwigslied” - Kamińska, Anna (Research in Language, 2007)
This paper presents an example of a historical study based on comparable corpora. It aims to analyse and compare the distribution of different parts of speech in Old English and Old High German, thus providing a quantitative basis for further conclusions concerning different patterns of the development of those two West-Germanic languages. A particular attention has been devoted to the frequencies of prepositions and pronouns, as there are considerable differences between the languages in this respect. In addition, the article is a an attempt to show the importance and relevance of computational data for contrastive historical linguistics and their role in supporting or disproving traditional theories.